Lingual Movement during Speech Production by a Speaker of Cantonese with Dysarthria-An Electromagnetic Articulographic Study - Manwa Lawrence Ng; Yang Chen; Sally Wong (康复学报)
Objective:To compare the differences of the lingual movement between a healthy volunteer and a stroke patient with Cantonese dysarthria, the lingual kinematic parameters were obtained by an electromagnetic articulograph (EMA).Methods:Lingual kinematic data were obtained from a Cantonese adult male who suffered from a stroke and an age-matched neurologically healthy adult male. For both subjects, an EMA was used to visualize, trace and record movement of the tongue during production of Cantonese single word production containing the six voiceless consonants (/t/,/th/,/k/,/kh/,/ts/,/tsh/,/s/) at word initial position. To describe the movement, four kinematic parameters including duration, displacement, velocity and acceleration values were obtained.Results:The study revealed a reduction of velocity, acceleration, but longer duration and tongue displacement for the speaker with dysarthria. In addition, lingual displacement associated with the error phonemes was similar to the substituted one (/t/), accounting for same phoneme perception.Conclusion:The EMA provided an objective measurement to better our understanding of the articulatory deviations exhibited by dysarthric individuals.